The role of foreign and domestic factors in the evolution of the Brazilian EMBI spread and debt dynamics - Andrea Fracasso (Graduate Institute of International Studies, 2007)
This paper examines the relative importance of global and domestic factors as a source of macroeconomic fluctuations in Brazil from 1995 to 2004. US and Brazilian credit spreads are encompassed in a near-VAR model, including the main debtrelated domestic variables. The US corporate bond spread is used as a measure of international risk aversion. The relative importance of global factors to the volatility of Brazilian domestic series is singled out by means of a partial identification strategy, whereby foreign variables are treated as block exogenous. The estimates reveal that foreign investors' appetite for risk is an important determinant of the volatility of the macroeconomic Brazilian series and affects the monetary policy transmission channel, as recently suggested by Olivier Blanchard.
Keywords: F34; F42; O23; E32; 330; External factors; Credit spreads; External debt; Fiscal dominance; Internationale Staatsschulden; Indexanleihe; Kreditrisiko; Brasilien